(3XGgQI ZSjd GdCehGds - (3SdjeGf(B, (3YHO GdefYes ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s, 2002)
(3ecGaMI ZSjd GdCehGd Ch GSJNOGe YGFOGJ GdLQGFe Ydi UYjO GdbGfhf GdLfGFj GdhWfj,UYhHGJ JLQje hedGMbI fTGW ZSjd GdCehGd habG ddChUGa GdLfGFjI GdJbdjOjI,eOi EYJHGQ ZSjd GdCehGd echfG dLQjeI ENaGA CTjGA PGJ eUOQ ZjQ eTQhY,VQhQGJ GdHMK Yf hUa LfGFj NGU dJLQje hedGMbI fTGW ZSjd GdCehGds
(3HHdjhZQGajG(B:(3U(B.172-176s
Keywords: (3GdHfhcs; (3GdMeGjI GdeUQajIs